A polyanionic sulfate positive electrode material and preparation method thereof

By doping carbon-based materials into polyanionic sulfate positive electrode materials and optimizing the preparation process, the problems of structural collapse and poor performance of existing materials during electrochemical sodium storage are solved, and high conductivity and excellent electrochemical performance are achieved.

CN116598448BActive Publication Date: 2025-04-15ZHEJIANG ZHONGZHE NEW ENERGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310500868.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-06
Publication Date
2025-04-15
Estimated Expiration
2043-05-06

AI Technical Summary

Technical Problem

The existing polyanionic sulfate positive electrode materials have problems such as structural collapse, irreversible oxidation of Fe elements and impurity phases during electrochemical sodium storage, resulting in poor electrochemical performance, and sodium storage capacity, cycle stability and high rate performance need to be improved.

Method used

By doping carbon-based materials into the positive electrode material, specifically a mixture formed by mixing fluorinated graphene, graphene and Super P at a specific mass ratio, and by reasonably selecting the precursor raw materials and process parameters, a polyanionic sulfate positive electrode material with excellent electrochemical properties is prepared.

Benefits of technology

It significantly improves the conductivity and performance stability of the positive electrode material, improves the electrochemical performance, cycling performance and high rate performance of sodium batteries, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a polyanionic sulfate positive electrode material and a preparation method thereof, and relates to the technical field of sodium batteries. x M y (SO4) z N n Sulfate represented by, wherein x, y, z, n are all positive real numbers, M includes Hf, Fe and rare earth elements, N includes Se and Cl; the mass of the carbon-based material is Na x M y (SO4) z N n The polyanionic sulfate cathode material disclosed in the present invention has high conductivity, good electrochemical performance, excellent charge and discharge performance, rate performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium battery electrode materials, and in particular to a polyanionic sulfate positive electrode material and a preparation method thereof. Background Art

[0002] In recent years, with the development of economy and the further advancement of global industrialization, problems such as excessive energy consumption and environmental pollution have become increasingly serious. Energy shortage and environmental degradation have become the core issues threatening human survival and development. The development of new renewable energy is imminent, and the demand for clean energy storage devices is increasing. Sodium batteries have become an ideal choice for large-scale clean energy storage technology due to their natural abundance and low cost of sodium, high safety, environmental friendliness, high energy density, and excellent electrochemical performance. They are expected to become the new favorite in the energy storage device market.

[0003] Positive electrode materials are an important component of sodium batteries, and they play a decisive role in improving electrochemical performance, improving energy density, and reducing the cost of the entire battery. At present, positive electrode materials for sodium batteries mainly include two categories: layered transition metal oxides and polyanionic compounds. The preparation process of layered transition metal oxide positive electrode materials is relatively complex, energy-intensive, expensive, and toxic. In addition, their sodium storage electrochemical performance is not outstanding, their sodium storage specific capacity is low, their working potential is not high, and their cycle performance and rate performance are poor. Polyanionic compound positive electrode materials are expected to become the first choice for sodium battery positive electrode materials due to their stable structure, high operating voltage, good safety performance, cycle stability, and high specific capacity. However, the electronic conductivity of this type of material is low, resulting in low utilization of active substances and partial loss of capacity, which makes it difficult to meet the requirements of high-rate charge and discharge of power batteries.

[0004] The Chinese patent with the authorization publication number CN108682827B discloses a carbon composite sodium ion positive electrode material and its preparation method, which successfully embeds the carbon-based material into the Na by solid phase mixing and sintering. x Fe y (SO4) z The material has low heat treatment temperature and simple production process, which inhibits the production of impurity phases and significantly improves the yield of the target material. However, the preparation method cannot effectively inhibit the irreversible oxidation of the Fe element and the formation of impurity phases during its preparation process, as well as the structural collapse caused by phase change or reaction stress enrichment during electrochemical sodium storage. The electrochemical performance of the obtained polyanionic sodium iron sulfate positive electrode material is not significant, and the sodium storage capacity, cycle stability and high rate performance need to be further improved.

[0005] It can be seen that the development of a polyanion positive electrode material with high electrical conductivity, good electrochemical properties, excellent charge and discharge performance, rate performance and cycle performance meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the sodium battery field. Summary of the invention

[0006] The main purpose of the present invention is to solve the above technical problems and provide a polyanionic sulfate positive electrode material with high conductivity, good electrochemical performance, excellent charge and discharge performance, rate performance and cycle performance and a preparation method thereof.

[0007] To achieve the above objectives, the present invention provides a polyanionic sulfate cathode material, comprising a carbon-based material doped with Na x M y (SO4) z N n Sulfate represented by, wherein x, y, z, n are all positive real numbers, M includes Hf, Fe and rare earth elements, N includes Se and Cl; the mass of the carbon-based material is Na x M y (SO4) z N n 0.5-10wt% of mass.

[0008] Preferably, the carbon-based material is a mixture of fluorinated graphene, graphene and Super P in a mass ratio of 1:(3-5):4.

[0009] Preferably, the fluorinated graphene has a sheet diameter of 0.5-2 μm, a thickness of 0.8 nm, and a model number of XF096, which is provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0010] Preferably, the graphene is a single-layer graphene with a thickness of 0.8-1.2 nm and a diameter of 0.5-5 μm, numbered XF001H, and provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0011] Preferably, the particle size of the Super P is 30-40 nm, and is provided by Shenzhen Weidifei New Energy Technology Co., Ltd.

[0012] Preferably, the M is a mixture of Hf, Fe and rare earth elements in a molar ratio of 0.5:10:(0.1-0.3).

[0013] Preferably, the rare earth element is at least one of lanthanum and cerium.

[0014] Preferably, the N is a mixture of Se and Cl in a molar ratio of 1:(0.8-1.2).

[0015] Another object of the present invention is to provide a method for preparing the polyanionic sulfate positive electrode material, comprising the following steps:

[0016] Step S1, preparation of precursor: ferrous sulfate monohydrate, sodium sulfate, sodium chloride, sodium selenide, hafnium sulfate, rare earth sulfate and carbon-based material are mixed, added into a high-speed ball mill, and ball milled at a speed of 300-500 rpm for 1.5-2.5 hours under an inert gas atmosphere to obtain a positive electrode material precursor;

[0017] Step S2, sintering: placing the cathode material precursor prepared in step S1 in a high-purity nitrogen atmosphere, heating it to 350-460°C at a heating rate of 3-5°C / min, sintering it for 12-20h, and naturally cooling it to obtain a polyanionic sulfate cathode material.

[0018] Preferably, the molar ratio of ferrous sulfate monohydrate, sodium sulfate and sodium selenide in step S1 is 1:1:(0.05-0.1).

[0019] Preferably, the rare earth sulfate in step S1 is at least one of lanthanum sulfate and cerium sulfate.

[0020] Preferably, the inert gas in step S1 is any one of nitrogen, helium, neon and argon.

[0021] Due to the application of the above technical solution, the present invention has the following beneficial effects:

[0022] (1) The preparation method of the polyanionic sulfate positive electrode material disclosed in the present invention has a simple preparation process, high raw material utilization rate, small impact on the environment, high preparation efficiency and finished product qualification rate, low dependence on equipment, and is suitable for efficient large-scale industrial production.

[0023] (2) The polyanionic sulfate cathode material disclosed in the present invention comprises a carbon-based material doped with Na x M y (SO4) z N n Sulfate represented by, wherein x, y, z, n are all positive real numbers, M includes Hf, Fe and rare earth elements, N includes Se and Cl; the mass of the carbon-based material is Na x M y (SO4) z N nThe carbon-based material is doped with 0.5-10wt% of the mass. The conductivity and the performance stability of the material can be significantly improved; the carbon-based material is a mixture formed by mixing fluorinated graphene, graphene, and Super P in a mass ratio of 1: (3-5): 4. Through the reasonable selection of the carbon-based material components, the carbon-based material can be added to the positive electrode material to effectively improve the electrochemical performance of the positive electrode material, so that the sodium battery using the positive electrode material has better battery efficiency and cycle performance.

[0024] (3) In the polyanionic sulfate cathode material disclosed in the present invention, the M is a mixture of Hf, Fe and rare earth elements at a molar ratio of 0.5:10:(0.1-0.3); and the N is a mixture of Se and Cl at a molar ratio of 1:(0.8-1.2). The doping of Hf, rare earth elements, Se and Cl can effectively improve the electrochemical properties of the cathode material, thereby improving the cycle capacity retention rate and the first charge and discharge efficiency.

[0025] (4) The polyanionic sulfate cathode material disclosed in the present invention further improves the cycle stability and high rate performance of the cathode material in the electrochemical sodium storage process through the reasonable selection of precursor raw materials and process parameters, and can better ensure the sodium storage specific capacity and rate performance. DETAILED DESCRIPTION

[0026] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations. Example 1

[0027] A polyanionic sulfate cathode material comprising a carbon-based material doped with Na x M y (SO4) z N n Sulfate represented by, wherein x, y, z, n are all positive real numbers, M includes Hf, Fe and rare earth elements, N includes Se and Cl; the mass of the carbon-based material is Na x M y (SO4) z N n 3wt% of mass.

[0028] The carbon-based material is a mixture of fluorinated graphene, graphene, and Super P in a mass ratio of 1:3:4; the flake diameter of the fluorinated graphene is 0.5-2 μm, the thickness is 0.8 nm, the model is XF096, and it is provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; the graphene is a single-layer graphene with a thickness of 0.8-1.2 nm and a diameter of 0.5-5 μm, numbered XF001H, and is provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; the particle size of the Super P is 30 nm, and it is provided by Shenzhen Weidifei New Energy Technology Co., Ltd.

[0029] The M is a mixture of Hf, Fe and rare earth elements in a molar ratio of 0.5:10:0.1; the rare earth element is lanthanum; and the N is a mixture of Se and Cl in a molar ratio of 1:0.8.

[0030] A method for preparing the polyanionic sulfate positive electrode material comprises the following steps:

[0031] Step S1, preparation of precursor: ferrous sulfate monohydrate, sodium sulfate, sodium chloride, sodium selenide, hafnium sulfate, rare earth sulfate and carbon-based material are mixed, added into a high-speed ball mill, and ball milled at a speed of 300 rpm for 1.5 hours under an inert gas atmosphere to obtain a positive electrode material precursor;

[0032] Step S2, sintering: placing the cathode material precursor prepared in step S1 in a high-purity nitrogen atmosphere, heating to 350° C. at a heating rate of 3° C. / min, sintering at this temperature for 12 hours, and naturally cooling to obtain a polyanionic sulfate cathode material.

[0033] The molar ratio of ferrous sulfate monohydrate, sodium sulfate and sodium selenide in step S1 is 1:1:0.05; the rare earth sulfate in step S1 is lanthanum sulfate; and the inert gas in step S1 is nitrogen. Example 2

[0034] A polyanionic sulfate cathode material comprising a carbon-based material doped with Na x M y (SO4) z N n Sulfate represented by, wherein x, y, z, n are all positive real numbers, M includes Hf, Fe and rare earth elements, N includes Se and Cl; the mass of the carbon-based material is Na x M y (SO4) z N n 5wt% of mass.

[0035] The carbon-based material is a mixture of fluorinated graphene, graphene, and Super P in a mass ratio of 1:3.5:4; the flake diameter of the fluorinated graphene is 0.5-2 μm, the thickness is 0.8 nm, the model is XF096, and it is provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; the graphene is a single-layer graphene with a thickness of 0.8-1.2 nm and a diameter of 0.5-5 μm, numbered XF001H, and is provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; the particle size of the Super P is 33 nm, and it is provided by Shenzhen Weidifei New Energy Technology Co., Ltd.

[0036] The M is a mixture of Hf, Fe and a rare earth element in a molar ratio of 0.5:10:0.15; the rare earth element is cerium; and the N is a mixture of Se and Cl in a molar ratio of 1:0.9.

[0037] A method for preparing the polyanionic sulfate positive electrode material comprises the following steps:

[0038] Step S1, preparation of precursor: ferrous sulfate monohydrate, sodium sulfate, sodium chloride, sodium selenide, hafnium sulfate, rare earth sulfate and carbon-based material are mixed, added into a high-speed ball mill, and ball milled at a speed of 350 rpm for 1.8 hours under an inert gas atmosphere to obtain a positive electrode material precursor;

[0039] Step S2, sintering: placing the cathode material precursor prepared in step S1 in a high-purity nitrogen atmosphere, heating to 380° C. at a heating rate of 3.5° C. / min, sintering for 15 h, and naturally cooling to obtain a polyanionic sulfate cathode material.

[0040] The molar ratio of ferrous sulfate monohydrate, sodium sulfate and sodium selenide in step S1 is 1:1:0.07; the rare earth sulfate salt in step S1 is cerium sulfate; and the inert gas in step S1 is helium. Example 3

[0041] A polyanionic sulfate cathode material comprising a carbon-based material doped with Na x M y (SO4) z N n Sulfate represented by, wherein x, y, z, n are all positive real numbers, M includes Hf, Fe and rare earth elements, N includes Se and Cl; the mass of the carbon-based material is Na x M y (SO4) z N n 6wt% of mass.

[0042] The carbon-based material is a mixture of fluorinated graphene, graphene, and Super P in a mass ratio of 1:4:4; the flake diameter of the fluorinated graphene is 0.5-2 μm, the thickness is 0.8 nm, the model is XF096, and it is provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; the graphene is a single-layer graphene with a thickness of 0.8-1.2 nm and a diameter of 0.5-5 μm, numbered XF001H, and is provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; the particle size of the Super P is 35 nm, and it is provided by Shenzhen Weidifei New Energy Technology Co., Ltd.

[0043] The M is a mixture of Hf, Fe and rare earth elements in a molar ratio of 0.5:10:0.2; the rare earth element is lanthanum; and the N is a mixture of Se and Cl in a molar ratio of 1:1.

[0044] A method for preparing the polyanionic sulfate positive electrode material comprises the following steps:

[0045] Step S1, preparation of precursor: ferrous sulfate monohydrate, sodium sulfate, sodium chloride, sodium selenide, hafnium sulfate, rare earth sulfate and carbon-based material are mixed, added into a high-speed ball mill, and ball milled at a speed of 400 rpm for 2 hours under an inert gas atmosphere to obtain a positive electrode material precursor;

[0046] Step S2, sintering: placing the cathode material precursor prepared in step S1 in a high-purity nitrogen atmosphere, heating to 410° C. at a heating rate of 4° C. / min, sintering for 16 h, and naturally cooling to obtain a polyanionic sulfate cathode material.

[0047] The molar ratio of ferrous sulfate monohydrate, sodium sulfate and sodium selenide in step S1 is 1:1:0.08; the rare earth sulfate in step S1 is lanthanum sulfate; and the inert gas in step S1 is neon. Example 4

[0048] A polyanionic sulfate cathode material comprising a carbon-based material doped with Na x M y (SO4) z N n Sulfate represented by, wherein x, y, z, n are all positive real numbers, M includes Hf, Fe and rare earth elements, N includes Se and Cl; the mass of the carbon-based material is Na x M y (SO4) z N n 9wt% of mass.

[0049] The carbon-based material is a mixture of fluorinated graphene, graphene, and Super P in a mass ratio of 1:4.5:4; the flake diameter of the fluorinated graphene is 0.5-2 μm, the thickness is 0.8 nm, the model is XF096, and it is provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; the graphene is a single-layer graphene with a thickness of 0.8-1.2 nm and a diameter of 0.5-5 μm, numbered XF001H, and is provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; the particle size of the Super P is 38 nm, and it is provided by Shenzhen Weidifei New Energy Technology Co., Ltd.

[0050] The M is a mixture of Hf, Fe and rare earth elements in a molar ratio of 0.5:10:0.25; the rare earth element is lanthanum; and the N is a mixture of Se and Cl in a molar ratio of 1:1.1.

[0051] A method for preparing the polyanionic sulfate positive electrode material comprises the following steps:

[0052] Step S1, preparation of precursor: ferrous sulfate monohydrate, sodium sulfate, sodium chloride, sodium selenide, hafnium sulfate, rare earth sulfate and carbon-based material are mixed, added into a high-speed ball mill, and ball milled at a speed of 450 rpm for 2.3 hours under an inert gas atmosphere to obtain a positive electrode material precursor;

[0053] Step S2, sintering: placing the cathode material precursor prepared in step S1 in a high-purity nitrogen atmosphere, heating to 450°C at a heating rate of 4.5°C / min, sintering for 18 hours, and naturally cooling to obtain a polyanionic sulfate cathode material.

[0054] The molar ratio of ferrous sulfate monohydrate, sodium sulfate and sodium selenide in step S1 is 1:1:0.09; the rare earth sulfate in step S1 is lanthanum sulfate; and the inert gas in step S1 is argon. Example 5

[0055] A polyanionic sulfate cathode material comprising a carbon-based material doped with Na x M y (SO4) z N n Sulfate represented by, wherein x, y, z, n are all positive real numbers, M includes Hf, Fe and rare earth elements, N includes Se and Cl; the mass of the carbon-based material is Na x M y (SO4) z N n 10wt% of mass.

[0056] The carbon-based material is a mixture of fluorinated graphene, graphene, and Super P in a mass ratio of 1:5:4; the flake diameter of the fluorinated graphene is 0.5-2 μm, the thickness is 0.8 nm, the model is XF096, and it is provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; the graphene is a single-layer graphene with a thickness of 0.8-1.2 nm and a diameter of 0.5-5 μm, numbered XF001H, and is provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; the particle size of the Super P is 40 nm, and it is provided by Shenzhen Weidifei New Energy Technology Co., Ltd.

[0057] The M is a mixture of Hf, Fe and rare earth elements in a molar ratio of 0.5:10:0.3; the rare earth element is cerium; and the N is a mixture of Se and Cl in a molar ratio of 1:1.2.

[0058] A method for preparing the polyanionic sulfate positive electrode material comprises the following steps:

[0059] Step S1, preparation of precursor: ferrous sulfate monohydrate, sodium sulfate, sodium chloride, sodium selenide, hafnium sulfate, rare earth sulfate and carbon-based material are mixed, added into a high-speed ball mill, and ball milled at a speed of 500 rpm for 2.5 hours under an inert gas atmosphere to obtain a positive electrode material precursor;

[0060] Step S2, sintering: placing the cathode material precursor prepared in step S1 in a high-purity nitrogen atmosphere, heating to 460° C. at a heating rate of 5° C. / min, sintering at this temperature for 20 hours, and naturally cooling to obtain a polyanionic sulfate cathode material.

[0061] The molar ratio of ferrous sulfate monohydrate, sodium sulfate and sodium selenide in step S1 is 1:1:0.1; the rare earth sulfate salt in step S1 is cerium sulfate; and the inert gas in step S1 is nitrogen.

[0062] Comparative Example 1

[0063] The present invention provides a polyanionic sulfate positive electrode material, the formula and preparation method of which are similar to those of Example 1, except that no fluorinated graphene and hafnium sulfate are added.

[0064] Comparative Example 2

[0065] The present invention provides a polyanionic sulfate positive electrode material, the formula and preparation method of which are similar to those of Example 1, except that sodium selenide and Super P are not added.

[0066] In order to further illustrate the beneficial technical effects of the polyanionic sulfate positive electrode material prepared in each embodiment of the present invention, the polyanionic sulfate positive electrode material prepared in each example was ground and mixed with a conductive agent Super P and a binder PVDF in a mass ratio of 85:5:10, and NMP was added to prepare a slurry with a solid-liquid ratio of 30% and magnetically stirred for 1 hour. After the slurry was evenly adjusted, the slurry was drawn on a 15 μm thick aluminum foil to form a positive electrode sheet. In an argon glove box, a metal sodium sheet was used as a negative electrode, a Celgard 2400 type diaphragm was used as a diaphragm, and 1 mol / L NaPF6 / PC was used as an electrolyte to assemble a CR2025 button battery; room temperature charge and discharge were carried out at a voltage range of 1.0 to 4.2 V and a current density of 0.1 C, and the first charge and discharge efficiency was recorded. At room temperature, the battery was charged at a constant current of 1C to 4.0V, then charged at a constant voltage to a current of 0.05C, and then discharged at a constant current of 1 / 3C to 1.0V. The capacity retention rate after 200 cycles of charge / discharge was calculated. The test results are shown in Table 1.

[0067] As can be seen from Table 1, the sodium ion battery using the polyanionic sulfate positive electrode material disclosed in the embodiment of the present invention has more excellent electrochemical performance and cycle performance than the comparative example product; the addition of graphene fluoride, sodium hafnium selenide sulfate and Super P is beneficial to improving the above performance.

[0068] Table 1

[0069] project First charge and discharge efficiency (%) Capacity retention after 300 cycles (%) Example 1 96.32 97.0 Example 2 96.38 97.3 Example 3 96.48 97.8 Example 4 96.70 98.6 Example 5 96.83 99.1 Comparative Example 1 92.18 92.8 Comparative Example 2 90.85 91.6

[0070] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.

Claims

1. A polyanionic sulfate cathode material, characterized in that: Containing carbon-based materials doped with Na x M y (SO4) z N n Sulfate represented by, wherein x, y, z, n are all positive real numbers, M includes Hf, Fe and rare earth elements, N includes Se and Cl; the mass of the carbon-based material is Na x M y (SO4) z N n 0.5-10wt% of mass.

2. The polyanionic sulfate cathode material according to claim 1, characterized in that: The carbon-based material is a mixture formed by mixing fluorinated graphene, graphene and Super P in a mass ratio of 1:(3-5):

4.

3. The polyanionic sulfate cathode material according to claim 2, characterized in that: The fluorinated graphene has a sheet diameter of 0.5-2 μm, a thickness of 0.8 nm, and a model number of XF096; the graphene is a single-layer graphene with a thickness of 0.8-1.2 nm, a diameter of 0.5-5 μm, and a model number of XF001H; and the particle size of the Super P is 30-40 nm.

4. The polyanionic sulfate cathode material according to claim 1, characterized in that: The M is a mixture of Hf, Fe and rare earth elements in a molar ratio of 0.5:10:(0.1-0.3).

5. The polyanionic sulfate cathode material according to claim 4, characterized in that: The rare earth element is at least one of lanthanum and cerium.

6. The polyanionic sulfate cathode material according to claim 1, characterized in that: The N is prepared by mixing Se and Cl in a molar ratio of 1:(0.8-1.2).

7. A method for preparing the polyanionic sulfate cathode material according to any one of claims 1 to 6, characterized in that: The steps include: Step S1, preparation of precursor: ferrous sulfate monohydrate, sodium sulfate, sodium chloride, sodium selenide, hafnium sulfate, rare earth sulfate and carbon-based material are mixed, added into a high-speed ball mill, and ball milled at a speed of 300-500 rpm for 1.5-2.5 hours under an inert gas atmosphere to obtain a positive electrode material precursor; Step S2, sintering: placing the cathode material precursor prepared in step S1 in a high-purity nitrogen atmosphere, heating it to 350-460°C at a heating rate of 3-5°C / min, sintering it for 12-20h, and naturally cooling it to obtain a polyanionic sulfate cathode material.

8. The method for preparing the polyanionic sulfate cathode material according to claim 7, characterized in that: The molar ratio of ferrous sulfate monohydrate, sodium sulfate and sodium selenide in step S1 is 1:1:(0.05-0.1).

9. The method for preparing the polyanionic sulfate cathode material according to claim 7, characterized in that: The rare earth sulfate salt in step S1 is at least one of lanthanum sulfate and cerium sulfate.

10. The method for preparing the polyanionic sulfate cathode material according to claim 7, characterized in that: The inert gas in step S1 is any one of nitrogen, helium, neon and argon.

Citation Information

Patent Citations

  • A carbon composite sodium ion cathode material and its preparation method

    CN108682827B

  • Application of lithium vanadium fluorophosphates / fluorinated graphene composite anode material in lithium ion capacitor

    CN107845507A

  • Iron-based sodium-ion battery positive electrode material and preparation method thereof

    CN110931784A